PREPARASI DYE SENSITIZED SOLAR CEL MENGGUNAKAN EKSTRAK ANTOSIANIN KULIT BUAH MANGGIS (Garcinia Mangostana L) - Maulina, Anna; Hardeli, Hardeli; Bahrizal, Bahrizal (Sainstek : Jurnal Sains dan Teknologi, 2014)
This study aims to determine the effect of the concentration of semi-solid electrolyte/polymer gel and determine the effect of the dye absorption technique on TiO2 paste the resulting DSSC efficiency. The results obtained by XRD characterization of TiO2 crystal phase is anatase and rutile TiO2 with a crystal size of 30.27 nm. Based of testing the light absorption of dye extract of purple sweet potato is known that the spectrum of the dye can absorb light at 533 nm wavelength maximum. The result of the conversion of sunlight into electrical energy obtained the highest value is at the highest PEG concentration at 0.1 M is 0,38% for TiO2 paste is mixed directly with the dye and 0,23% for TiO2 paste soaking in the dye for 24 hours using an electrolyte semi-solid/gel polymer with an area of 1 cm2.Key words: Anthocyanin, DSSC, semi-solid electrolyte, FTIR, UV-Vis, XRD